Spectroscopy of the T = 2 mirror nuclei 48Fe/48Ti using mirrored knockout reactions - R. Yajzey (Elsevier, 2021)
A sequence of excited states has been established for the first time in the proton-rich nucleus 48Fe (Z=26, N=22). The technique of mirrored (i.e. analogue) one-nucleon knockout reactions was applied, in which the Tz= ±2 mirror pair, 48Fe/48Ti were populated via one-neutron/one-proton knockout from the secondary beams 49Fe/49V, respectively. The analogue properties of the reactions were used to help establish the new level scheme of 48Fe. The inclusive and exclusive cross sections were determined for the populated states. Large differences between the cross sections for the two mirrored reactions were observed and have been interpreted in terms of different degrees of binding of the mirror nuclei and in the context of the recent observations of suppression of spectroscopic strength as a function of nuclear binding, for knockout reactions on light solid targets. Mirror energy differences (MED) have been determined between the analogue T=2 states and compared with the shell model predictions. MED for this mirror pair, due to their location in the shell, are especially sensitive to excitations out of the f7/2 shell, and present a stringent test of the shell-model prescription.